Inherited variation in the PARP1 gene and survival from melanoma. Issue 7 (6th March 2014) - Davies, John R.; Jewell, Rosalyn; Affleck, Paul; Anic, Gabriella M.; Randerson‐Moor, Juliette; Ozola, Aija; Egan, Kathleen M.; Elliott, Faye; García‐Casado, Zaida; Hansson, Johan; Harland, Mark; Höiom, Veronica; et al.
Abstract : We report the association of an inherited variant located upstream of the poly(adenosine diphosphate‐ribose) polymerase 1 ( PARP1 ) gene (rs2249844), with survival in 11 BioGenoMEL melanoma cohorts. The gene encodes a protein involved in a number of cellular processes including single‐strand DNA repair. Survival analysis was conducted for each cohort using proportional hazards regression adjusting for factors known to be associated with survival. Survival was measured as overall survival (OS) and, where available, melanoma‐specific survival (MSS). Results were combined using random effects meta‐analysis. Evidence for a role of the PARP1 protein in melanoma ulceration and survival was investigated by testing gene expression levels taken from formalin‐fixed paraffin‐embedded tumors. A significant association was seen for inheritance of the rarer variant of PARP1, rs2249844 with OS (hazard ratio (HR) = 1.16 per allele, 95% confidence interval (CI) 1.04–1.28, p  = 0.005, eleven cohorts) and MSS (HR = 1.20 per allele, 95% CI 1.01–1.39, p  = 0.03, eight cohorts). We report bioinformatic data supportive of a functional effect for rs2249844. Higher levels of PARP1 gene expression in tumors were shown to be associated with tumor ulceration and poorer OS. Abstract : What's New? Although staging systems predict outcome fairly well for melanoma, survival still varies among individual patients. In this meta‐analysis, the authors found that inheritance of a rare genetic variant of PARP1 was associated with improved survival of melanoma patients. Increased expression of PARP1 has been associated with poorer outcome, and depletion of PARP1 may reduce both melanoma growth and angiogenesis. The identification of this and other germline variants that affect survival may help to identify key biological pathways active in host/tumor interactions, which may lead to the discovery of new therapeutic targets for treating advanced melanoma.